Hukum Musik Dalam Perspektif Saddu Dzara’i - Abduh, Muhammad; Tanjung, Dhiauddin (Tabayyun : Journal Of Islamic Studies, 2024)
This article aims to explain how the law of music is in the perspective of saddu dzara'i. The issue of whether music is haram or not is still an interesting discussion at this time. The Salafis consider that music is absolutely haram, while Ibn Hazm allows music to be used to invite goodness. This research is qualitative research which is carried out by collecting, analyzing, and interpreting the narrative comprehensively on visual data to obtain a complete, comprehensive, and holistic insight into the law of music in the perspective of saddu dzara'i. The results of this study show that a music has two law, there are halal and haram based on their respective reasons. Music becomes halal when it is used for good purposes and is not mixed with disobedience and Music becomes haram if it is used for a bad purpose and contains inadversity such as the designation of pornography.